Alterations of serum high sensitive C reactive protein and lipid levels in newly diagnosed myocardial infarction subjects - Aparna, R. R.; Rajeswari, D. Raja; Ramalingam, K.; Kumar, R. Viswa; Balakrishna, D. (International Journal of Research in Medical Sciences, 2019)
Background: Acute Myocardial Infarction (AMI) is one of the major causes of mortality in the world. Atherosclerosis leading to AMI is the most common and severe clinical manifestation observed. Dyslipidemia is one of main traditional risk factor for MI, but in more than 50% of CHD events dyslipidemia was absent. Atherosclerosis is considered as both a chronic inflammatory condition and a disorder of lipid metabolism. The present study was aimed to estimate the levels of serum lipids (total cholesterol, LDL cholesterol, HDL cholesterol) and hs-CRP an inflammatory marker in newly diagnosed AMI cases and to find out any correlation between these two. Methods: The study was conducted on 50 newly diagnosed myocardial infarction cases, admitted in Cardiology Department Narayana Medical College, Nellore. Both the sexes were included. Fifty age and sex matched healthy individuals were selected as controls. Lipid levels are estimated by end point colorimetric assay (HUMANSTAR kit) and hs-CRP was estimated by immunofluorescence technique (Boditechkit). Results: Significant raised levels of hs-CRP (p value <0.0001) and low HDL cholesterol (p value =0.0085) levels among the cases was noticed. A significant positive correlation was observed between LDL cholesterol and hsCRP (r=0.109, p=0.040). A non-significant positive correlation between hsCRP and HDL cholesterol (r=0.291, p=0.453) was observed. Conclusions: The results of the study implicate the role of inflammatory component in causing atherosclerosis or coronary artery disease rather than dyslipidaemias alone to be attributed for atherogenesis. Concomitantly HDL cholesterol levels were found to be low in cases that results from the inflammatory component in atherogenesis.